Analysis of Turberculosis-COVID-19 Coinfection Using Fractional Derivatives - Samuel Okyere; Joseph Ackora-Prah; Saleem Abdullah; Samuel Akwasi Adarkwa; Frank Kofi Owusu; Kwame Bonsu; Mary Osei Fokuo; Mary Ann Yeboah (International Journal of Mathematics and Mathematical Sciences)
Fractional-order derivative modeling continues to receive great interest among researchers across the globe. In this study, Tuberculosis-COVID-19 coinfection is studied using Atangana–Baleanu fractional-order derivatives defined in Caputo sense. We confirmed the existence and singularity of the solution and investigated the model’s equilibrium points. Additionally, we examined the model’s stability in terms of the Ulam–Hyers and generalized Ulam–Hyers stability criteria. The basic reproduction number R0 was calculated using the next-generation matrix approach. We also looked into the model’s disease-free equilibrium point’s regional stability. Numerical scheme for simulating the fractional-order system with Mittag–Leffler Kernels are presented. Numerical simulations are given to validate the model. Results of the simulation showed a decline in the number of COVID-19 infections within the population when the fractional operator was reduced.